Antioxidant Activity and Phenolic Content of Microwave-Assisted Solanum melongena Extracts. (9th February 2014) - Salerno, Loredana; Modica, Maria N.; Pittalà, Valeria; Romeo, Giuseppe; Siracusa, Maria A.; Di Giacomo, Claudia; Sorrenti, Valeria; Acquaviva, Rosaria
Abstract : Eggplant fruit is a very rich source of polyphenol compounds endowed with antioxidant properties. The aim of this study was to extract polyphenols from eggplant entire fruit, pulp, or skin, both fresh and dry, and compare results between conventional extraction and microwave-assisted extraction (MAE). The effects of time exposure (15, 30, 60, and 90 min) and solvent (water 100% or ethanol/water 50%) were also evaluated. The highest amount of polyphenols was found in the extract obtained from dry peeled skin treated with 50% aqueous ethanol, irradiated with microwave; this extract contained also high quantity of flavonoids and showed good antioxidant activity expressed by its capacity to scavenge superoxide anion and to inhibit lipid peroxidation.